Housing policy and economic development: the Croatian case - Zlatan Fröhlich (European Regional Science Association (ERSA), 2002)
Housing in Croatia is beset with many problems, as reflected in a dramatic fall in new housing construction, low housing standards, absence of streamlined policy which would encourage housing construction, as well as ambiguous regulations governing this area. Transition from planned to market economy requires far-reaching and comprehensive changes in the whole institutional framework, from central government structures to the private sector. This is particularly true of the housing sector which under the previous socio-economic system had a special political and social place. Transformation and introduction of new institutional structures required for a successful development of the housing sector in Croatia is one of the main bottlenecks within that sector. This particularly applies to local authorities, non-profit housing associations and the private sector. However, what is still missing is the main leverage required for organising the housing activities at the national level - and these are appropriate financial instruments, in the sense that they are not developed enough to enable the housing sector to really contribute to Croatia's economic and social development. To be more specific, it is necessary to provide financial instruments and paper will deal with proposals for the national housing finance policy. Namely, what will be checked too, is a gradual shift of general state support mechanisms towards direct public financing of priority projects, for example, in the form of subsidies. Subsidy financing would be efficiently concentrated on the housing projects enjoying a general public and political priority, such as low-cost housing construction for young families/first-time homebuyers or social housing projects of local authorities or projects of non-profit housing associations based on rental and controlled prices of new housing units. In the future restructuring of local administration and self-government units allowance will have to be made for the need to clearly define responsibilities in order to ensure efficiency in implementing the housing policies. This topic will be particularly emphasized in the paper as well as the role of non-profit housing associations and banking sector. At the end will be presented an outline of the key elements of the housing sector in Croatia as seen by the Expert Group to highlight the main bottlenecks in the sector and to propose the future actions of the national housing strategy.
Keywords: 330